Cardiovascular Risk Factors as Differential Predictors of Incident Atypical and Typical Major Depressive Disorder in US Adults. Issue 6 (July 2018) - Patel, Jay S.; Berntson, Jessica; Polanka, Brittanny M.; Stewart, Jesse C.
ABSTRACT: Objective: Although the association between major depressive disorder (MDD) and future cardiovascular disease (CVD) is established, less is known about the relationship between CVD risk factors and future depression, and no studies have examined MDD subtypes. Our objective was to determine whether hypertension, tobacco use, and body mass index (BMI) differentially predict atypical and typical MDD in a national sample of US adults. Methods: We examined prospective data from 22, 915 adults with no depressive disorder history at baseline who participated in Wave 1 (2001–2002) and Wave 2 (2004–2005) of the National Epidemiologic Survey on Alcohol and Related Conditions. CVD risk factors (Wave 1) and incident MDD subtypes (Wave 2) were determined by structured interviews. Results: There were 252 patients with atypical MDD and 991 patients with typical MDD. In fully adjusted models, baseline hypertension (odds ratio [OR] = 0.57, 95% confidence interval [CI] = 0.43–0.76), former tobacco use (OR = 1.46, 95% CI = 1.20–1.78), and BMI (OR = 1.32, 95% CI = 1.25–1.40; all p < .001) predicted incident atypical MDD versus no MDD, whereas no CVD risk factor predicted incident typical MDD. Baseline hypertension (OR = 0.52, 95% CI = 0.39–0.70), former tobacco use (OR = 1.53, 95% CI = 1.22–1.93), and BMI (OR = 1.26, 95% CI = 1.18–1.36; all p < .001) also predicted incident atypical MDD versus typical MDD. Conclusions: Our study is the first to report that CVD risk factors differentially predict MDD subtypes, with hypertension (protective factor), former tobacco use (risk factor), and BMI (risk factor) being stronger predictors of incident atypical versus typical MDD. Such evidence could provide insights into the etiologies of MDD subtypes and inform interventions tailored to MDD subtype. Abstract : Supplemental digital content is available in the text.